Dark zone of the Greenland Ice Sheet controlled by distributed biologically-active impurities - Ryan, Jonathan C.; Hubbard, Alun Lloyd; Stibal, Marek; Irvine-Fynn, Tristam D.; Cook, Joseph; Smith, Lawrence C.; Cameron, Karen; Box, Jason E (Nature Communications, 2018)
Source at http://doi.org/10.1038/s41467-018-03353-2. Albedo—a primary control on surface melt—varies considerably across the Greenland Ice Sheet yet the specific surface types that comprise its dark zone remain unquantified. Here we use UAV imagery to attribute seven distinct surface types to observed albedo along a 25 km transect dissecting the western, ablating sector of the ice sheet. Our results demonstrate that distributed surface impurities—an admixture of dust, black carbon and pigmented algae—explain 73% of the observed spatial variability in albedo and are responsible for the dark zone itself. Crevassing and supraglacial water also drive albedo reduction but due to their limited extent, explain just 12 and 15% of the observed variability respectively. Cryoconite, concentrated in large holes or fluvial deposits, is the darkest surface type but accounts for <1% of the area and has minimal impact. We propose that the ongoing emergence and dispersal of distributed impurities, amplified by enhanced ablation and biological activity, will drive future expansion of Greenland's dark zone.